Egzystencjalno-religijny model przywództwa biznesowego. Perspektywa holistyczna - Marek, Agnieszka; Kostrzewa, Sylwia (Annales. Etyka w Życiu Gospodarczym, 2020)
The main aim of the paper is to show an existential religious model of business leadership. We want to defend the thesis that leaders, who consider existing norms and regulations, have the greatest influence on how organisational aims are achieved. Thus, based on the concept of Kierkegaard’s modes of existence, we show that the individual values and motives of leaders’ behaviour influence the shape of the leadership itself as well as the management of an organisation. On the basis of a literature review, we propose the following connections: an aesthetic mode with instrumental motives which result in the shareholder perspective; an ethical mode of existence with normative motives which lead to the stakeholder perspective; and the spiritual mode of existence with transcendental motives which enable leaders to introduce a holistic perspective of management. However, we cannot link certain motives with a particular type of leadership, as leaders with different modes of existence might practice the same type of leadership (i.e., leadership based on values, authentic leadership) and combine various types of leadership in their actions. The paper might provide a theoretical basis for empirical research on leadership and managerial behaviour.